Desain Kapal Wisata Jenis Pinisi di Perairan Indonesia Timur - Arif Fadillah Fadillah; Bondan Kartika Ibrahim; Shanty Manullang (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
Pinisi, the name of a traditional ship from Sulawesi which has 7 to 8 of sail characteristics. The ship, which was made without using engineering methods or calculations, has sailed the ocean since the 18th century and proved to be a seaworthy ship. Mainly used as an inter-island transportation of goods which in the future loses its old function and becomes antiques used as a liveaboard type tourist ship. This tourist ship is widely used in eastern Indonesia such as Labuan Bajo, North Sulawesi, Raja Ampat and areas rich in sea beauty suitable for liveaboard. This research designed the pinisi liveaboard ship, discusses the determination of the ship main size with a Comparison method of several ship geometries such as the ratio of length and width, width and draft, etc. Trial and Error methods are used in the design of General Arrangement and Interior Design. By Comparison, Trial and Error methods, the main size of the ship is LOD = 33.0 m, B = 9 m, H = 3.5 m, T = 2.8 m, Cb = 0.591 with Vs = 9 Knots. From this dimension, General Arrangement and Interior Facility were designed and visualize.